La Biblioteca della Külliye di Kavála Descrizione del fondo locale e ricostituzione del patrimonio librario dell'istituto - Bruni, Barbara (Scuole di dottorato, 2005)
This study represents the continuation and in part the completion of a research study within an Islamic educational and philanthropic institution, currently located in Greek territory. Through repeated inspections and a long work of comparison, not only have the volumes kept at the institution of Kavála been catalogued, but the composition of the entire library has also been almost entirely reconstructed, identifying additional funds belonging to it. Furthermore, the research examines the implications useful for delineating both the cultural profile of the Institution and a particular historical phase for the methodological and content innovations introduced in the transmission of knowledge within the Islamic world.